Placenta accreta spectrum disorder: An updated literature review - Mirani, Putri; Lestari, Peby Maulina; Murti, Krisna; Liberty, Iche Andriyani; Andrina, Hana; Kesty, Cindy; Stevanny, Bella (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Placenta accreta spectrum disorder (PASD) refers to a range of pathological placental adhesions to the uterine wall, previously classified into three subtypes: placenta accreta, placenta increta, and placenta percreta, based on the invasiveness of the villous tissue. This article provides an updated review of the literature on PASD with new insights into the etiopathology of PASD. Recent evidence suggests that extravillous trophoblasts are not overly invasive and that accreta placentation is more likely due to decidualisation failure resulting from blastocyst implantation within a caesarean scar defect (CSD). Previous caesarean delivery has been the most well-known risk factor of PASD, with the increased occurrence of PASD along with the increased number of previous caesarean deliveries. Antenatal identification of PASD is strongly recommended to improve outcomes before the onset of labour or bleeding, so that placental abruption can be avoided. Ultrasonography can identify PASD in the first trimester with good sensitivity and specificity. A standardised approach with a comprehensive multidisciplinary care team is required to manage PASD effectively. The Royal College of Obstetricians and Gynaecologists (RCOG), along with The American College of Obstetricians and Gynaecologists (ACOG), have published guidelines for the best clinical management of PASD. Future research should concentrate on gathering prospective data on the diagnosis and management of PASD in order to assess the association between prenatal imaging, clinical grading, and histology findings. This will lead to more accurate PASD screening, reliable diagnostic criteria, and alternatives to prenatal treatment.